Farm Telecast in Kerala - A critical appraisal - Sobha S. (Department of Agricultural Extension, College of Agriculture, 2013)
This study entitled ‘Farm Telecast in Kerala – a Critical Appraisal’ was carried out in fifteen panchayats of Thiruvananthapuram, Kollam and Alappuzha districts.